Acquired Hemophilia A: A Rare, Acquired Coagulopathy in the Postpartum Setting - Oberlin, Austin; Krenitsky, Nicole M.; Gandhi, Christy; Akpan, Imo Joseph; Eisenberger, Andrew; Landau, Ruth; Yurteri-Kaplan, Ladin; Nathan, Lisa; Sheen, Jean-Ju; LaSala, Anita; D'Alton, Mary (American Journal of Perinatology Reports, 2023)
Postpartum hemorrhage (PPH) remains a leading cause of maternal morbidity. Pregnancy-associated acquired hemophilia A (AHA) caused by autoantibodies against factor VIII can present with recurrent episodes of postpartum bleeding.Case 1 A 50-year-old G2P0112 presented with vaginal bleeding 22 days postcaesarean. She underwent dilation and curettage, hysterectomy, and interventional radiology (IR) embolization before AHA diagnosis. She was hospitalized for 32 days and received 23 units of blood product. She remains without relapse of AHA after 5 years.Case 2 A 48-year-old G3P1021 presented with vaginal bleeding 8 days postcaesarean. She underwent three surgeries and IR embolization before AHA diagnosis. She was hospitalized for 18 days and received 39 units of blood product. Prednisone and cyclophosphamide were continued after discharge.AHA is a rare cause of PPH. An isolated prolonged activated partial thromboplastin time (aPTT) should prompt further workup in postpartum patients with refractory bleeding. Rapid recognition of AHA can prevent significant morbidity related to hemorrhage, massive transfusion, and multiple surgeries.
Keywords: postpartum hemorrhage; bleeding disorder; coagulopathy; maternal morbidity